2023
DOI: 10.1021/acs.jpcc.3c01557
|View full text |Cite
|
Sign up to set email alerts
|

Significant Enhancement of Optoelectronic Properties in CuInP2S6 via Pressure-Induced Structural Phase Transition

Abstract: Quaternary layered transition metal thiophosphate CuInP2S6 (CIPS) has attracted extensive research interest because of its outstanding optical and ferroelectric properties. Pressure-tuned phase transition is an efficient method to regulate the properties of functional materials in situ, yet there is still much to explore. Herein, we studied the pressure-regulated optoelectronic properties of CIPS and found a four-stage evolution of photoresponsivity under compression. The photoresponse of CIPS barely changes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Pressure, as a fundamental thermodynamic parameter, has been viewed as an effective means to regulate the physical and chemical properties of materials without introducing impurities. Based on the pressure strategy, extensive research studies on the fundamental properties of materials have been reported, including pressure-induced phase transition, metallization, and pressure-enhanced photoluminescence, superconductivity, and photocurrents. It has been reported that the optical properties of ZnSiP 2 can be significantly regulated by external pressure, as well as an emergent superconductivity occurs at 24.6 GPa . Lattice dynamical calculations indicated that ZnSnP 2 undergoes an order–disorder transition at around 6.5 GPa .…”
Section: Introductionmentioning
confidence: 99%
“…Pressure, as a fundamental thermodynamic parameter, has been viewed as an effective means to regulate the physical and chemical properties of materials without introducing impurities. Based on the pressure strategy, extensive research studies on the fundamental properties of materials have been reported, including pressure-induced phase transition, metallization, and pressure-enhanced photoluminescence, superconductivity, and photocurrents. It has been reported that the optical properties of ZnSiP 2 can be significantly regulated by external pressure, as well as an emergent superconductivity occurs at 24.6 GPa . Lattice dynamical calculations indicated that ZnSnP 2 undergoes an order–disorder transition at around 6.5 GPa .…”
Section: Introductionmentioning
confidence: 99%